An updated and comprehensive review of the antiviral potential of essential oils and their chemical constituents with special focus on their mechanism of action against various influenza and coronaviruses. (March 2021) - Wani, Abdul Rouf; Yadav, Kanchan; Khursheed, Aadil; Rather, Manzoor Ahmad
Abstract: Essential oils and their chemical constituents have been reported with well documented antimicrobial effects against a range of bacterial, fungal and viral pathogens. By definition, essential oils are a complex mixture of volatile organic compounds which are synthesized naturally in different parts of the plant as part of plants secondary metabolism. The chemical composition of the essential oils is dominated by the presence of a range of compounds including phenolics, terpenoids, aldehydes, ketones, ethers, epoxides and many others inferring that essential oils must be effective against a wide range of pathogens. This review article mainly focuses on the antiviral potential of essential oils and their chemical constituents especially against influenza and coronaviruses. Essential oils have been screened against several pathogenic viruses, including influenza and other respiratory viral infections. The essential oils of cinnamon, bergamot, lemongrass, thyme, lavender have been reported to exert potent antiviral effects against influenza type A virus. The essential oil of Citrus reshni leaves has been shown to be effective against H5N1 virus. The essential oil of Lippia species at a concentration of 11.1 μg/mL has been shown to induce 100% inhibition of yellow fever virus in Vero cells. Essential oils and oleoresins have been shown through in vitro and in vivo experiments to induce antiviral effects against Coronavirus infectious bronchitis virus. A study reported 221 phytochemical compounds and essential oils to be effective against severe acute respiratory syndrome associated coronavirus (SARS-CoV) using a cell-based assay measuring SARS-CoV-induced cytopathogenic effect on Vero E6 cells. The main mechanism of antiviral effects of essential oils has been found to cause capsid disintegration and viral expansion which prevents the virus to infect host cells by adsorption via the capsid. Essential oils also inhibit hemagglutinin (an important membrane protein of various viruses) of certain viruses; this membrane protein allows the virus to enter the host cell. Many essential oils and their components could inhibit the late stages of viral life cycle by targeting the redox signalling pathway. Essential oils of Thymus vulgaris, cymbopogon citratus and Rosmarinus officinalis have been found to destabilize the Tat/TAR-RNA complex of HIV-1 virus, this complex being essential for HIV-1 replication. Being lipophilic in nature, essential oils can penetrate viral membranes easily leading to membrane disintegration. The current comprehensive review will facilitate researchers to find chemical entities from plant sources as possible inhibitory agents against various viruses. Graphical abstract: Image 1 Highlights: Large number of published studies report significant antiviral effects of essential oils. Essential oils cause capsid disintegration and viral expansion making them ineffective. Inhibition of hemagglutinin (membrane protein) of certain viruses has been reported by essential oils. Essential oils destabilize the Tat/TAR-RNA complex of HIV-1 virus, which is essential for viral replication. Being lipophilic in nature, essential oils can easily penetrate viral membranes leading to membrane disruption.